2011
DOI: 10.1590/s1516-89132011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragments' contribution to the natural biological control of Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Maize

Abstract: The present work evaluated the influence of forest distance on predatory solitary wasps' abundance and richness and its relation to the natural biological control of the fall armyworm (Spodoptera frugiperda Smith - Lepidoptera: Noctuidae) in maize. The study consisted of two parallel lines of six experimental maize plots located at an increasing distance from a forest edge. Four trap-nests were placed in the vertices of each plot of the first line to evaluate the abundance and species richness of predatory sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
2
12
1
4
Order By: Relevance
“…Here we provide empirical evidence that forest remnants are sources of natural enemies of a widespread and costly pest in coffee, and that the proportion of forest cover on the landscape increases biodiversity and ecosystem services in a Neotropical region. Similarly, previous studies conducted in Brazil found that forest remnants increase the abundance and diversity of beneficial insects including bees , syrphids , parasitoids (Bortolotto et al, 2016) and predatory wasps (Sousa et al, 2011) in adjacent agroecosystems. Thus, we recommend that agri-environment schemes in Brazilian agricultural landscapes should focus on the conservation of forest remnants and forest restoration in areas of low agricultural importance, abandoned crops and riparian areas at multiple spatial scales.…”
Section: Implication For Conservation and Policiessupporting
confidence: 62%
“…Here we provide empirical evidence that forest remnants are sources of natural enemies of a widespread and costly pest in coffee, and that the proportion of forest cover on the landscape increases biodiversity and ecosystem services in a Neotropical region. Similarly, previous studies conducted in Brazil found that forest remnants increase the abundance and diversity of beneficial insects including bees , syrphids , parasitoids (Bortolotto et al, 2016) and predatory wasps (Sousa et al, 2011) in adjacent agroecosystems. Thus, we recommend that agri-environment schemes in Brazilian agricultural landscapes should focus on the conservation of forest remnants and forest restoration in areas of low agricultural importance, abandoned crops and riparian areas at multiple spatial scales.…”
Section: Implication For Conservation and Policiessupporting
confidence: 62%
“…Therefore, forest fragments should also possess heterogeneous and diverse ecotones to support the large predator communities that are important for open habitats (e.g. wasps), and which can serve as biocontrol agents in adjacent patches (Lichtenberg & Lichtenberg, ; Sousa et al ., ). Our results show that there is a wide range of potential predators of insects in the different parts of trees and a possibly high risk of predation at ground level.…”
Section: Discussionmentioning
confidence: 97%
“…In Brazil, some studies have evaluated the effects of fragments of native forest on natural enemies, in crops such as: Eucalyptus (Eucalyptus spp.) (Murta et al, 2008), corn (Zea mays L.) (Sousa et al, 2011) and sugar cane (Saccharum officinarum L.) (Demite et al, 2015;Duarte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%